(untitled) (LACCEI, 2024)
The world is facing unprecedented challenges due to the COVID-19 pandemic, this situation has slowed development progress in many countries. The pandemic has had a very strong impact on human capital: many lives, education, basic well-being, and future productivity were taken. Many countries have become increasingly concerned with the pandemic, which necessitates research in new information technologies. This includes artificial intelligence research. One new idea we present in this paper helps to fight the epidemic. Very little research has been conducted on mask detection. This is because masks provide protection against COVID-19, and people with masks struggle to function normally without protection. However, recent advances in CNNs have made it possible to extract deep features from faces.